Reducing medication errors for hospital inpatients with Parkinsonism. Issue 3 (18th March 2021) - Lance, Sean; Travers, Justin; Bourke, David
Abstract: Background: Patients with Parkinsonism are 1.5 times more likely than comparators to be hospitalised and have a significantly longer length of stay in hospital. Medication delays, inappropriate medication omission, and administration of contraindicated medications likely contribute to these poor outcomes. Education and hospital system interventions may reduce these errors. Aim: To determine the effectiveness of a multimodal education and awareness campaign in reducing medication errors in patients with Parkinsonism at Hutt Hospital. Methods: We performed an audit of hospital medication charts to establish the baseline medication error rate and patient outcomes over a 3‐month period. We then delivered an intervention consisting of staff education sessions, a sticker alert system and increased priority for pharmacist review of patient drug charts. We repeated the audit after the intervention. Results: In the initial audit, the medication error rate was 22.5%, the clinical complication rate was 45% and one death was directly attributable to medication error. At follow up, the medication error and complication rates were 9.3% (absolute difference 13% (95% conflict of interest (CI) 10–16.4), P < 0.001) and 38% (absolute difference 7% (95% CI −19 to 34), P = 0.59), respectively, and there were no attributable deaths. The average length of stay before and after the intervention was 13 and 8 days respectively (absolute difference 5.7 days (95% CI −1.8 to 13.3), P = 0.135). Conclusions: There was a high in‐hospital medication error rate for Parkinsonian patients. The intervention resulted in a statistically significantly improvement in the medication error rate. The estimated reductions in complication rate and length of stay may be clinically important. Similar interventions may be beneficial in other institutions.